CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Lactose-decorated, alginate-coated chitosan nanoparticles loaded with Coomassie Brilliant Blue G-250 protect colonic barrier integrity in experimental colitis - Maha M. Amer; Ahmed Y. Kira; Sameh Saber; Abdulaziz A. Alsalloom; Mostafa M. Khodeir; Hala A. Elashry; Rabab S. Hamad; Adel Alhomaidi; Hamad Alsaykhan; Mohammed Alorini; Mohamed R. Abdel-Hamed; Huda Eltayeb; et al. (Tissue and Cell, 2026)

Agri-food waste valorization through Monascus ruber fermentation for natural pigment production: bioconversion efficiency, neuroprotective potential, and functional food relevance - El-Sayed R. El-Sayed; Anna Dunal; Witold Pietrzak; Ewelina Opiela; Joanna Grzelczyk; Grażyna Budryn; Horacio Pérez-Sánchez; Jorge Ricardo Alonso Fernández; Filip Boratyński (Food Chemistry, 2026)

Novel production of vinblastine by immobilized cultures of mutant strain of the endophytic Alternaria alternata - El-Sayed R. El-Sayed; Rofaida S. Abdelkader; Heba S. Moustafa; Samah A. Yousef; Mohamed A. Taha; Sahar M. Ouda (World Journal of Microbiology and Biotechnology, 2026)

Exploring the therapeutic potential of Lupeol isolated from Ochrosia elliptica Labill. leaves in polycystic ovarian syndrome - Essam Abdel-Sattar; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Shimaa R. Emam; Heba Hozyen; Marwa Zakaria; Samar M. Mouneir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

From sensitivity to diagnosis: a composite soil degradation index for conservation planning in arid lands - Mohamed A. E. AbdelRahman; Ali R. A. Moursy; Moatez A. El-Sayed; Alaa H. Abdel-Azeem (Applied Geomatics, 2026)

Geospatial Insights into Land Use Dynamics: Remote Sensing and GIS for Agricultural Sustainability in Assiut and Minya, Egypt - R. A. Ali Moursy; A. E. Mohamed AbdelRahman; M. Hassan Al-Sayed; M. Ahmed Ali; A. Moatez El-Sayed (Agricultural Research, 2026)

Correction: Geospatial Insights into Land Use Dynamics: Remote Sensing and GIS for Agricultural Sustainability in Assiut and Minya, Egypt - R. A. Ali Moursy; A. E. Mohamed AbdelRahman; M. Hassan Al-Sayed; M. Ahmed Ali; A. Moatez El-Sayed (Agricultural Research, 2026)

Microbial fuel cells for sustainable energy and wastewater treatment: Integrating seaweed biomass, machine learning, and hybrid systems for enhanced performance - Indah Izza Muwakhidah; Monika Sharma; Adel I. Alalawy; Nahla S. Zidan; Mohamed Sakran; Abdulaziz R. Alqahtani; Guozhao Jia; El-Sayed Salama (Bioresource Technology, 2026)

Ursolic acid, a pentacyclic triterpene from Ochrosia elliptica Labill leaves and its role in the management of polycystic ovary syndrome (PCOS) - Shimaa R. Emam; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Heba F. Hozyen; Marwa Zakaria; Essam A. Abdel-Sattar; Samar M. Mouneir (Inflammopharmacology, 2026)
Ursolic Acid (UA), a naturally occurring pentacyclic triterpene, was isolated from Ochrosia elliptica . Polycystic Ovary Syndrome (PCOS) a prevalent endocrine disorder characterized by hyperandrogenism, insulin resistance, and chronic inflammation. In this study, we investigate the role of UA in alleviating the symptoms of PCOS, focusing on its biochemical, hormonal, and histopathological effects in a rat model. Using adult female Wistar Albino rats, PCOS was induced through letrozole administration. The rats were then treated with UA at two different doses (25 and 50 mg/kg), alongside a control group and a standard ovulation-inducing medication, clomiphene citrate (1 mg/kg). Biochemical analyses showed that PCOS induction significantly increased serum malondialdehyde (MDA) levels by approximately 1.21-fold, while markedly reducing superoxide dismutase (SOD) and catalase (CAT) activities ( p ≤ 0.05) by approximately 0.48-fold, relative to negative control. Treatment with UA (50 mg/kg) dose-dependently restored oxidative balance, reducing MDA (~ 0.82-fold) and elevating SOD (~ 2.39-fold) and CAT (~ 2.11-fold) activities toward PCOS values ( p ≤ 0.05). Hormonally, PCOS rats exhibited elevated luteinizing hormone (LH) and testosterone levels by approximately 1.70-fold, compared to the negative control ( p ≤ 0.05). Both doses of UA significantly lowered LH and testosterone, with the 50 mg/kg dose achieving reductions comparable to clomiphene citrate ( p ≤ 0.05). Histopathological examination showed improved ovarian morphology with reduced cystic follicles and increased corpus lutea in UA-treated groups. Furthermore, UA downregulated key genes involved in steroidogenesis and oxidative stress response, suggesting a multifaceted mechanism of action. The findings highlight UA’s potential as a novel therapeutic option for managing PCOS symptoms, emphasizing the need for further research into its efficacy and safety in clinical applications.

Compost-mixed Biochar Improves Saline Soil Properties and Enhances Brassica Oleracea var. Capitata physio-biochemical Responses - Ahmed R. Abd EL-Tawwab; Abdelsattar Abdelkhalik; Ahmed Shaaban; Basma R. Abdel-Moatamed; Khaulood A. Hemida; Ali A.S. Sayed; Mostafa M. Rady; Hani S. Saudy; Mohammed A.H. Gyushi (Journal of Soil Science and Plant Nutrition, 2026)
The present research aimed to correlate changes in saline soil properties and cabbage agro-physiological attributes under compost-biochar co-application. The treatments used prior to cabbage cultivation were soil applications of compost/biochar mixtrure (CMB) at rates of 0 (CMB 0 ), 10 (CMB 10 ), and 20 (CMB 20 ) t ha –1 in a randomized complete block design with three replications. The CMB 20 was the effective practice for reducing dry bulk density, saturated hydraulic conductivity, pH, and electrical conductivity, while improving total porosity, water-holding pores, soil moisture at field capacity, organic matter, cation exchange capacity, and nutrient availability. CMB 20 also improved plant relative water content, membrane stability index, and chlorophyll a and b concentrations. Hydrogen peroxide and malondialdehyde decreased by 13.5% each under CMB 20 treatment. Cabbage plants grown in saline soil produced greater phenolics content (56.0%) with higher superoxide dismutase (17.2%) activity in CMB 20 -treated plots than CMB 0 . Leaf nitrogen, phosphorus, and potassium contents enhanced by 10.1, 28.1, and 18.4%, respectively, compared with CMB 0 . Finally, CMB 20 achieved the maximal improvements in leaf number plant − 1 (41.8%), leaf area plant − 1 (216.2%), above-ground biomass (174.5%), head circumference (38.2%) and marketable yield (101.6%) of cabbage. It could be concluded that amending saline soil with CMB is regarded as a promising treatment for alleviating the salinity hazards on cabbage via modulating soil properties and physiological responses. Hence, CMB application, 20 t ha –1 , can be recommended as an agronomic practice for cabbage production to obtain high yield and quality.

Controls on the emplacement of the arc-related Um Rus pluton, central Egyptian Nubian Shield - Mona A. El- Harairey; Hoda R. Saad; Haytham Sehsah; El Sayed I. Selim; Ahmed Elbahrawy (Journal of African Earth Sciences, 2026)

Hydrogen sulphide modifies the therapeutic potential of bone marrow mesenchymal stem cells in an adjuvant-induced polyarthritis rat model through the mitigation of angiogenesis, ectopic lymphoid tissue formation, and osteoclastogenesis - Sara M. El-Sayed; Mohamed R. Mohamed; Mohamed M. Naguib; Hadeer A. Aglan; Hanaa H. Ahmed (Inflammopharmacology, 2026)
Among the chronic and progressive autoimmune disorders that primarily affect joints in the hands, wrists, and knees, rheumatoid arthritis (RA) is a highly prevalent one. A significant number of patients develop severe adverse events, display weak responses, or cannot afford long-term use of the current RA medications, requiring more efficient and safer curative alternatives. increasing evidence recommends the application of mesenchymal stem cells (MSCs)-based therapy for mitigating chronic inflammation and boosting tissue renewal in intractable disorders. Moreover, sodium hydrosulphide (NaHS) has recently been found to have anti-inflammatory effects. Therefore, this study compared the therapeutic outcomes of four approaches; bone marrow-derived mesenchymal stem cells (BM-MSCs), their conditioned media (CM), BM-MSCs pre-conditioned with NaHS, and their conditioned media in a rat model of adjuvant-induced polyarthritis. The process involved the isolation of MSCs from rat bone marrow, propagation, and characterization of the isolated cells. polyarthritis was induced in male Wistar rats via intradermal injection of type II collagen on day 0 and day 21. Affected rats were treated with naproxen, BM-MSCs, BM-MSCs-CM, NaHS, BM-MSCs preconditioned with NaHS, or BM-MSCs preconditioned with NaHS-CM. The results indicated that the administered cells homed to the bone marrow and bone trabeculae of the knee joint tissue of the afflicted rats. The proposed treatments brought about significant down-regulation of peptidyl arginine deiminase 2 (PAD2) and chemokine ligand 13 (CXCL13) genes as well as angiopoietin-1 (Ang-1) protein expression, along with substantial upregulation of the galectin-1 (GAL-1) gene and osteoprotegerin (OPG) protein expression. Compared with BM-MSCs therapy, the treatment with BM-MSCs preconditioned with NaHS and their CM exhibited superior effect, with values close to those of the controls. In addition, treatment with the CM of BM-MSCs offered a lesser effect compared to BM-MSCs therapy alone. In conclusion, NaHS has the potential to improve the therapeutic capability of BM-MSCs for RA in rats by enhancing their anti-inflammatory, immunomodulatory, and regenerative capacity.

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

Efficacy and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis: a randomized controlled study - Tarek M. Mostafa; Abeer A. El-Sayed; Abdel Moaty A. Afifi; Dalia R. El-Afify (European Journal of Clinical Pharmacology, 2025)
Objective This research aimed at evaluating the effectiveness and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis (RA). Methods In this randomized controlled parallel study, 90 patients with active RA were randomized into three groups; group 1 (control group; n = 30) which received traditional therapy, group 2 (Nitazoxanide group; n = 30) which received traditional therapy plus 1 gm/day oral nitazoxanide, and group 3 (Escitalopram group; n = 30) which received traditional therapy plus 10 mg/day oral escitalopram for three months. At baseline and 3 months after treatment, clinical and functional assessments were done through the 28-joint count disease activity score using C-reactive protein (DAS28-CRP), the health assessment questionnaire-disability index (HAQ-DI), and the patient’s global assessment (PGA). Also, serum levels of high-sensitivity C-reactive protein (hs-CRP), signal transducer and activator of transcription-3 (STAT-3), Janus kinase-2 (JAK-2), toll-like receptors 4 (TLR-4), interleukin-1 beta (IL-1β), and malondialdehyde (MDA) were assessed. Data were analyzed using paired t -test and one-way analysis of variance, followed by Tukey’s HDS test. Results Three months after treatment and as compared to the control group, the nitazoxanide group showed a significant decline in PGA ( P = 0.042), and serum levels of STAT-3 ( P < 0.001), JAK-2 ( P < 0.001), TLR-4 ( P < 0.001), and IL-1β ( P < 0.001). On the other hand, the escitalopram group produced a significant decrease in DAS28-CRP score ( P = 0.029), HAQ-DI score ( P = 0.001), and serum levels of JAK-2 ( P = 0.001), TLR-4 ( P < 0.001), IL-1β ( P < 0.001), and MDA ( P < 0.001). As compared to nitazoxanide group, the escitalopram group produced a significant decline in fatigue score ( P < 0.001) and serum levels of both IL-1β ( P = 0.023) and MDA ( P < 0.001). Both medications were safe; however, chromaturia was the only significant nitazoxanide-related adverse effect. Conclusion Nitazoxanide and escitalopram could serve as potential adjuvant therapies for patients with RA based on their effectiveness and safety data.

Tailoring the pore structure of mesoporous composite agro-based adsorbents for the enhanced removal of Cu(II) and Ni(II) heavy metal ions from wastewater - Rajesh M. Bhagat; Shantanu R. Khandeshwar; Amit B. Ranit; Mangesh P. Bhorkar; Bhupesh P. Nandurkar; Sagar Shelare; Shubham Sharma; N. Beemkumar; S. Hemalatha; Parveen Kumar; Ankit Kedia; Ehab El Sayed Massoud (Clean Technologies and Environmental Policy, 2025)

Dietary supplementation of ewes with Astragalus membranaceus root extract enhanced the feto-maternal hemodynamics, fetoplacental development, and lambs’ growth rate - Hossam R. El-Sherbiny; Fady Sayed Youssef; Mohammed Hamed Eldawy; Ismail Abdelraouf Elnady; Emad Mohammed Elken; Mohammed Hamdy Farouk; Ahmed Ezzat Ahmed; Maha Abdullah Momenah; Ramya Ahmad Sindi; Seham Samir Soliman; Haney Samir (Small Ruminant Research, 2025)

Preconditioning of bone marrow mesenchymal stem cells with sodium hydrosulfide enhances their therapeutic potential in type II collagen–induced arthritis rat model - Sara M. El-Sayed; Hanaa H. Ahmed; Hadeer A. Aglan; Mohamed M. Naguib; Mohamed R. Mohamed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
This study was conducted to evaluate the impact of sodium hydrogen sulfide (NaHS) on the therapeutic efficacy of bone marrow mesenchymal stem cells (BM-MSCs) in the treatment of collagen-induced arthritis (CIA) rats. MSCs were isolated and cultured from rat bone marrow, and their characteristics were determined. The CIA model was induced in rats by intradermal injections of type II collagen on days 0 and 21. A variety of treatments were administered, including naproxen, BM-MSCs, BM-MSC-conditioned media, NaHS, BM-MSCs preconditioned with NaHS, and BM-MSCs preconditioned with NaHS-conditioned media. The infused BM-MSCs homed to the bone trabeculae and cartilage of the knee joint, leading to significant improvements in gait scores and a reduction in paw withdrawal frequency (PWF). Treatment with BM-MSCs and NaHS also significantly suppressed serum levels of CRP, RF, and 14-3-3η, while downregulating TNF-α gene expression and MMP-1 protein levels in the synovial membrane. Histopathological analysis confirmed these biochemical and molecular genetic findings. Notably, CIA rats treated with BM-MSCs preconditioned with NaHS showed the most significant improvements, with outcomes closely resembling those of healthy controls. This study concludes that NaHS enhances the therapeutic efficacy of BM-MSC therapy for rheumatoid arthritis (RA) by augmenting their anti-inflammatory, immunomodulatory, and regenerative properties.

Preparation and optimization of eco-friendly inorganic geopolymer membrane - A. M. El-Sayed; H. Abdallah; M. Abdel-Goad; R. Abobeah; Sh. K. Amin (International Journal of Environmental Science and Technology, 2025)
The most common and widely used technique for water and wastewater treatment is membrane separation. This research was applied to fabricate an eco-friendly, low-cost, and sustainable geopolymer membrane that can be used in water treatment. A geopolymer membrane is fabricated using fired clay brick waste, the effect of several variables on the apparent porosity, compressive strength of the membrane, iron and manganese rejection was studied using response surface methodology, the studied variables are zeolite addition in the range of 0–25% by weight, curing temperature at the range from 50 to 90 °C and curing time ranging from 1 to 3 days. According to experimental results, the optimum membrane is prepared using only fired clay brick waste, cured at 70 °C for 1 day. Long-term performance test and fouling test were performed to ensure membrane durability, thus the flux recovery ratio was 97.94%, while the total fouling ratio was 3.66%, of which 1.6% was reversible. These membranes were further characterized through Fourier transform infrared spectroscopy, scanning electron microscope, and pore size distribution, and the results confirmed that the membrane had micropores with an average pore diameter of 0.1212 µm. The optimum membrane was used in a real water application and the manganese and iron rejection reached 99.8% and 90% respectively.

Eco-friendly composite membranes of recycled PVC and Co-MOFs for efficient Ca2+ scale removal and anti-fouling in water treatment - Mennat Allah M. Ali; Mona El-Sayed; Omnia A.A. El-Shamy; Ghada E. Khedr; Magdy W. Sabaa; Riham R. Mohamed; Mahmoud F. Mubarak (Process Safety and Environmental Protection, 2025)

Fungi – important biocatalysts in production of natural pigments and fragrances - Filip Boratyński; El-Sayed R. El-Sayed; Ewa Szczepańska; Stefano Serra (Phytochemistry Letters, 2025)

Unlocking bioactivity of endophytic fungi from Mokrzański Forest in Wroclaw, Poland - El-Sayed R. El-Sayed; Filip Boratyński; Joanna Grzelczyk (Phytochemistry Letters, 2025)

Adsorption of light green dye using Mg–Al-layered double hydroxides (LDHs) with carbonate and nitrate anions - S. F. Al-Furhud; R. M. K. Mohamed; I. Alsohaimi; M. M. Kamel; M. Y. El-sayed; H. M. Youssef; A. M. Aldawsari; H. M. A. Hassan (International Journal of Environmental Science and Technology, 2025)

Microplastics monitoring in different environments: separation, physicochemical characterization, and quantification - Wenbo Kong; Mabkhoot Alsaiari; Mohammed Jalalah; Farid A. Harraz; Habib Ullah; Abdulaziz R. Alqahtani; El-Sayed Salama (Environmental Monitoring and Assessment, 2025)

Insight into Apert Syndrome: Reporting on Six Patients and Increasing Awareness - Hala T. El-Bassyouni; Ghada Y. El-Kamah; Hanan H. Afifi; Mohamed B. Taher; Doaa R. Soliman; Khaled Hamed; Mennat I. Mehrez; Khalda Sayed Amr (Molecular Neurobiology, 2025)
Apert syndrome (AS) is a rare autosomal dominant disorder characterized by various congenital malformations. In this study, we aimed to explore the clinical presentation of Apert syndrome to enhance awareness among multidisciplinary healthcare providers regarding its differential diagnosis through the phenotype/genotype characterization of six Egyptian patients with AS. We examined six patients with Apert syndrome: four females and two males (2:1), aged 3 to 7 years. Clinical examination, along with pedigree analysis, was followed by DNA extraction from the patients’ and their parents’ peripheral blood leukocytes for genomic screening of FGFR2 gene variations. Key findings in all patients included craniosynostosis and distinctive facial features such as midface hypoplasia, exophthalmos, hypertelorism, a beaked nose, a prominent forehead, and an underdeveloped upper jaw, along with syndactyly of the hands and feet. We identified oral anomalies such as cleft palate, bifid uvula, impacted teeth, delayed eruption, supernumerary teeth, and thick gingiva. Pathogenic variants of the FGFR2 gene were characterized in all six patients. This report presents the largest cohort of Apert syndrome among Egyptian patients. Raising awareness about AS, especially among various interdisciplinary teams, is essential for managing this rare condition and is crucial for accurate diagnosis and timely medical and surgical intervention. Proper diagnosis and genetic counseling are necessary for improving survival and preventing the recurrence of complications.

Harnessing the Microbiome: CRISPR-Based Gene Editing and Antimicrobial Peptides in Combating Antibiotic Resistance and Cancer - Radwa A. Amen; Yaser M. Hassan; Rawan A. Essmat; Rana H. Ahmed; Marwan M. Azab; Nadia R. Shehata; Mariam M. Elgazzar; Wael M. El-Sayed (Probiotics and Antimicrobial Proteins, 2025)
The growing crisis of antibiotic resistance and the increasing incidence of cancer have prompted the exploration of innovative approaches, such as gene editing and antimicrobial peptides (AMPs). The human microbiome is integral to various aspects of health, disease, and therapeutic development, influencing metabolic pathways, immune function, and pathogen resistance. Recent advances in gene editing technologies, particularly CRISPR (clustered regularly interspaced short palindromic repeats), have opened new avenues for leveraging the microbiome to address complex medical challenges, including combating multidrug-resistant pathogens and cancer. The microbiome plays a crucial role in combating antibiotic resistance by modulating microbial communities, influencing pathogen survival and susceptibility to treatments. This review explores the microbiome’s dynamic role in metabolic regulation, its contribution to cancer management, and how AMPs help maintain homeostasis and exhibit emerging anticancer properties, supported by both preclinical findings and clinical evidence. Additionally, CRISPR-based microbiome engineering offers potential to enhance host-microbiome interactions, optimizing therapeutic outcomes. The integration of microbiome metagenomics and proteomics has led to the discovery of novel AMPs with targeted anticancer effects. Innovative strategies, such as engineered probiotics and CRISPR-based microbiome engineering, present exciting prospects for next-generation therapies. Despite these advances, the translation of microbiome-based therapies into clinical settings remains challenging due to ethical, regulatory, and ecological hurdles. This review underscores the transformative potential of microbiome-based interventions, emphasizing the role of personalized medicine in maximizing therapeutic efficacy. Furthermore, we also address critical research gaps, limitations, and future directions, including optimizing AMP stability, delivery, and bioavailability, as well as overcoming the regulatory and ethical challenges in clinical translation.

Physical purification of Egyptian bentonite clay as a sustainable binder of El-Dekheila-iron-oxide-waste - Ahmed A. Khalifa; El-Sayed R. E. Hassan; A. M. Elbendari; Rasha Amin; M. A. Abdel-Khalek (Euro-Mediterranean Journal for Environmental Integration, 2025)

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Metabolite profiling of Cucurbita pepo L. in relation to its potential to combat experimental trichinosis - Nashwa R. Mohamed; Seham S. El-Hawary; Fatema R. Saber; Ibrahim E. Sallam; Shaimaa H. El-Sayed (South African Journal of Botany, 2025)

Nanoliposomal Encapsulation of Red, Yellow, and Orange Natural Pigments from Monascus ruber: Characterization, Stability, and Biological Activities - Anita Dudek; Magdalena Pietrzak; Dominika Benkowska-Biernacka; Hanna Pruchnik; Filip Boratyński; El-Sayed R. El-Sayed (Current Microbiology, 2025)

Zinc-based metal–organic frameworks for sustainable water desalination and anti-scaling solutions - Mennat Allah M. Ali; Mona El-Sayed; Omnia A. A. El-Shamy; Ghada E. Khedr; Magdy W. Sabaa; Riham R. Mohamed; Mahmoud F. Mubarak (Environmental Science and Pollution Research, 2025)

Assessing seawater intrusion impact on groundwater quality in El-Omayed aquifers, Mediterranean coast, Egypt using hydrogeochemical and chemometric analyses - Mohammed I.A. Ibrahim; Mohamed A. El-Sawy; Ahmed R. Elgendy; Hossam M. El-Sayed; Laila A. Mohamed; Mohamed A. Aly-Eldeen (Groundwater for Sustainable Development, 2025)

Targeting TREM-1 receptors with metformin and pravastatin modulate monosodium iodoacetate-induced osteoarthritis - Eman R. Al Sawy; Mona M. Saber; Noha N. Nassar; Nesrine S. El Sayed (Inflammopharmacology, 2025)
Osteoarthritis (OA), a degenerative joint condition, affects entire joints, including the tissues around it, causing pain, swelling and stiffness. This study explored the combined therapeutic effects of metformin and pravastatin on knee OA induced by monosodium iodoacetate (MIA) in rats. The study encompassed five animal groups ( n = 10 per group) which were allocated as follows: group 1 received 100 µL of sterile saline injected intra-articularly into the left knee joint (control group) while groups 2–5 were injected with 2 mg MIA in 100µL normal saline into the intraarticular space. After 2 weeks, group 3 received oral metformin (100 mg/kg) for 2 weeks, group 4 received oral pravastatin (10 mg/kg) for 2 weeks and group 5 received both metformin 100 mg/kg and pravastatin 10 mg/kg orally for 2 weeks. The combination of metformin and pravastatin showed to be the most effective in terms of improving radiologic and histologic findings in knee OA. This combination also reduced both serum C reactive protein (CRP) and cartilage oligomeric matrix protein (COMP), while increasing serum collagen type II (COL2). Combining metformin and pravastatin also reduced AKT1, PI3K, STAT3 and IL-6 in the knee joint homogenate. TREM-1 levels showed the greatest reduction with the combination therapy. Furthermore, improvement was noted in oxidative stress markers with an increase in non-protein thiols and a decrease in malondialdehyde. In conclusion, the current study shows a therapeutic potential effect of combining metformin and pravastatin in OA, which could be partly attributed to TREM-1 signaling pathway. Graphical abstract

Structural and Energetic Insights into the Binding of L- and D-Arginine Analogs with Neuropilin-1 (NRP1): Molecular Docking, Molecular Dynamics and DFT Calculations - Mahmoud A. A. Ibrahim; Dina E. M. Mohamed; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Shaban R. M. Sayed; Mohamed A. El-Tayeb; Peter A. Sidhom; Paul W. Paré (Cell Biochemistry and Biophysics, 2025)

Identification of Components of the Sex Pheromone of the kōwhai Moth, Uresiphita Polygonalis Maorialis, a New Zealand Native Crambid - Ashraf M. El-Sayed; A. R. Gibb (Journal of Chemical Ecology, 2025)
The identification of sex pheromones in native New Zealand moths has been limited, largely due to their minimal pest impact on agricultural ecosystems. The kōwhai moth, Uresiphita polygonalis maorialis , a native crambid, is known for its herbivory on Sophora spp. and Lupinus arboreus leaves. Understanding the chemical ecology of this species is essential for studying its behavior, population dynamics, and ecological interactions. In this study, the female sex pheromone of U. polygonalis maorialis was analyzed using coupled gas chromatography-electroantennogram detection (GC-EAD). This approach identified four antennally active compounds in the female gland extracts. Subsequent gas chromatography-mass spectrometry (GC-MS) and chemical derivatization revealed these compounds to be tetradecyl acetate (14:Ac), (E)-11-tetradecenyl acetate (E11-14:Ac), (Z)-11-tetradecenyl acetate (Z11-14:Ac), and (Z)-11-hexadecenyl acetate (Z11-16:Ac). Field trapping experiments evaluated various combinations of these four EAD-active compounds and (E)-11-hexadecenyl acetate (E11-16:Ac). Results indicated that traps baited with blends containing E11-14:Ac, Z11-14:Ac, and Z11-16:Ac captured significantly more males compared to unbaited delta traps. A blend ratio of 144:84:72 µg (E11-14:Ac: Z11-14:Ac: Z11-16:Ac) proved the most effective, capturing the highest number of males. Male captures were recorded from late November to late February, peaking in late December, suggesting a univoltine population in Canterbury. Among the three tested doses, the 300 µg and 1000 µg doses of the three-component blend were the most effective. The identification of the sex pheromone components of U. polygonalis maorialis provides a valuable tool for monitoring this species, contributing to a deeper understanding of its population densities and distribution within its native range. It also offers insights into the evolutionary development of pheromone communication within the genus, shedding light on species divergence and adaptation.

Salinity-dependent effects of integrated biofloc technology on reproductive performance, biological responses, and offspring quality in red tilapia aquaculture - Ghada R. Sallam; Mohammed F. El Basuini; Amal F. Fahmy; Mohamed A. Al-Absawey; Yusuf Jibril Habib; Rahma Ahmed Mustafa; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Akram Ismael Shehata (Aquaculture International, 2025)
The study aims to evaluate the reproductive performance, serum biochemical indices, growth, antioxidant capacity, and immune response of Florida Red Tilapia ( Oreochromis sp.) progeny reared at different salinity levels within biofloc technology (BFT) systems, focusing on egg production, fertilization rates, tolerance to oxidative stress, and offspring performance. Broodstock reared in biofloc systems (BF) were compared to those in clear water (Without biofloc, WBF) across three salinity levels (18, 28, and 36‰) over a 7-month period. The study also assessed the tolerance of fry reared in biofloc systems to direct transfer to high salinity (36‰) without prior acclimatization. A total of 216 females (initial body weight: 182 ± 1.8 g) and 72 males (initial body weight: 201 ± 0.88 g) were randomly assigned to 18 concrete tanks (2 × 6 × 1 m) to investigate the effects of BFT on spawning performance and larval survival under high-salinity conditions. The findings indicated that appropriate salinity (18‰) in BFT systems positively affected reproductive efficiency, enhanced immunological parameters, and improved growth performance, but elevated salinity levels (36‰) led to reduced reproductive success and hindered growth performance. Florida red tilapia thrive in water quality conditions that are within acceptable limits. High salinity environments led to increased dissolved oxygen but reduced pH, especially in BFT ponds. BFT improved reproductive performance, reduced spawning time, and increased egg production. It also improved hatchability, larval quality, and yolk sac absorption. The BFT broodstock showed higher levels of key proteins (total protein, albumin, and globulin) and improved immune parameters, which helped counteract the negative effects of elevated salinity and enhanced their overall health and stress tolerance. In high-salinity environments, offspring in BFT systems showed higher survival rates and growth rates. In conclusion, BFT improves the reproductive performance, growth, and immune response of Florida red tilapia under high salinity. It enhances egg production, hatchability, and larval survival, while also improving water quality and immune function, making it a sustainable solution for tilapia aquaculture in saline environments.

Effect of a single dose of letrozole on ejaculation time, semen quality, and testicular hemodynamics in goat bucks subjected to heat stress - Ola Adel; Hossam R. El-Sherbiny; Abdallah M. Shahat; Sayed Taha Ismail (Veterinary Research Communications, 2024)
Letrozole (LTZ) is an aromatase inhibitor that limits estrogen (E2) production and increases testosterone (T) levels. This research aimed to examine the impact of a single dose of LTZ on testicular hemodynamics, ejaculation time, and semen quality in goats under heat stress (HS). Therefore, Doppler examination and semen evaluation were performed on twelve mature bucks for two weeks (W-1, W-2) as pre-heat stress control during winter. Then during summer HS bucks were subjected to Doppler examination, semen evaluation, and hormonal analysis (T, E2, and LH) at 0 h. Afterward, bucks were assigned into two groups and subcutaneously injected with physiological saline ( n = 6; CON) or LTZ (0.25 mg/kg BW; n = 6; LTZ). Both groups were subjected to Doppler scanning and hormonal analysis at 2, 4, 24, 48, 72, 96,144, and 168 h. Semen evaluation was performed at 48 and 168 h. The LTZ group showed increasing ( P < 0.05) in semen volume, sperm motility, and viability and decreasing ( P < 0.05) in ejaculation time and sperm abnormalities compared to CON group at 48 h. Additionally, T concentrations increased ( P < 0.01) at 2, 24, and 48 h, E2 decreased ( P < 0.01) from 2 to 48 h, and LH raised ( P < 0.01) at 2 and 72 h in LTZ group compared to CON one. Doppler indices reduced ( P < 0.05) at 96 h in LTZ group. semen pH and scrotal circumference were not affected by LTZ. In conclusion, LTZ administration shortened ejaculation time and enhanced semen quality in bucks during HS.

Association between Apo B, LDL-R and PCSK9 gene polymorphisms with coronary artery diseases in Egyptians - Nancy Mahsoub; Ahmed Almenshawy; Ahmed Mohammad Taki Eldin; Nehal M. Abdel Hay; Amany R. Youssef; Reham M El-Farahaty; Kefaya El-Sayed; Adel Mohamad Osman; Eman S. Elhennawy (Molecular Biology Reports, 2024)

Retraction Note: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s Disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2024)

Compilation of secondary metabolites produced by fungal strains identified as Aspergillus flavus var. oryzae (formerly Aspergillus oryzae), with a review of biotechnological applications, and computational studies of their anti-COVID-19 activity - Sabrin R. M. Ibrahim; Flavia Pinzari; Shaimaa G. A. Mohamed; Hazem G. A. Hussein; Abdulrahim A. Alzain; Mohammed A. Almogaddam; Ahmed H. E. Hassan; Selwan M. El-Sayed; Nada A. S. O. AlGhamdi; Gamal A. Mohamed (Mycological Progress, 2024)

Integrated biofloc technology in red tilapia aquaculture: Salinity-dependent effects on water quality, parental stock physiology, reproduction, and immune responses - Ghada R. Sallam; Akram Ismael Shehata; Mohammed F. El Basuini; Yusuf Jibril Habib; Shimaa Henish; Afaf N. Abdel Rahman; Youssef M. Hassan; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Hadir A. Aly (Aquaculture International, 2024)
The study examines the impact of integrated biofloc technology (BFT), different salinity levels, and their combined effects over 90 days on various physiological parameters. The investigation includes growth performance and feed utilization, water quality, the chemical composition of biofloc and fish, digestive enzymes, reproductive performance, stress and biochemical indicators, and antioxidant-immune responses in red tilapia ( Oreochromis spp .) broodstock. The fish were initially weighed (males: n = 270; 104 ± 0.96 g; females: n = 270; 93.2 ± 0.66 g) and subsequently divided into 12 treatment groups (6 for males and 6 for females) spread across 36 separate tanks (3 tanks per treatment; 45 fish per treatment; 15 fish/tank). The treatments involved three salinity levels (18, 28, and 36 ppt) in both clear water (CW) and BFT systems. The outcomes demonstrated that fish in the 36 ppt salinity with BFT treatment demonstrated significant improvements ( P P P

The Egyptian Nile estuarine habitats: a review - Khaled M. Abdelsalam; Hermine R. Z. Tadros; Abeer A. Moneer; Mona Kh. Khalil; Samia K. Hamdona; Laila Shakweer; Madelyn N. Moawad; Abeer A. M. El-Sayed; Ghada F. El-Said; Mona M. Ismail; Aida H. Shobier; Shimaa Hosny; et al. (Aquatic Sciences, 2024)
Estuaries are nutrient-rich environments characterized by a gradient in salinity due to the mixing of freshwater and seawater. These bodies of water play vital functions in nature and provide a wide variety of essential ecosystem services. In general, many natural and/or man-made activities have strongly stressed the Egyptian Nile estuarine habitats, as has the water shortage that was expected after the construction of the Grand Ethiopian Renaissance Dam. In recent decades, the Nile Delta has been considered to be one of the most important productive oil-producing petroleum regions due to onshore and offshore gas discoveries alongside gasoline and base oil generation. Up-to-date systematic reviews of the Egyptian estuarine habitats (Rosetta and Damietta) are missing, and the review reported here was undertaken to fill this gap. In this review, we consider the physical, chemical, geological, pollution, and biological parameters of Egyptian Nile estuaries. In this context, our aim is to contribute to a broader understanding of the Egyptian estuarine habitat; moreover, we provide potential warning signals that may aid in estuarine environmental protection. We found that most of the previous studies had focused on the two branches of the Nile or on the marine waters adjacent to these branches, and that only a few studies focused on the estuarine habitats themselves. In most of these previous studies, the salinity gradient of water was reported to be a significant factor in the distribution of the different measured parameters while, in contrast, more recent investigations confirm the importance of potential effluent sources in affecting the distribution of these parameters. We highly recommend that the data reported here be updated in future studies on different environmental aspects.

The Possible Neuroprotective Effect of Caffeic Acid on Cognitive Changes and Anxiety-Like Behavior Occurring in Young Rats Fed on High-Fat Diet and Exposed to Chronic Stress: Role of β-Catenin/GSK-3B Pathway - Norhan S. El-Sayed; Nehal Adel Khalil; Samar R. Saleh; Rania G. Aly; Marianne Basta (Journal of Molecular Neuroscience, 2024)

Investigation on the key mix design parameters of slag-based geopolymer concrete - Nada M. Nagy; Ismail Amer; El-Sayed A. R. Nasr; Mohamed Kohail (Innovative Infrastructure Solutions, 2024)

Impact of novel chloride-binding on strength, chloride penetration and resistance to corrosion of concrete exposed to chloride-bearing environment - Esraa S. Ibrahim; Mahmoud Gharieb; Mohamed R. Sakr; Hamdy A. El-Sayed; Mohamed O. R. El Hariri (Innovative Infrastructure Solutions, 2024)

Immunomodulatory and antioxidant properties of Sarcophaga argyrostoma larval hemolymph: utilizing the Biomphalaria alexandrina snail as a model - Alya Mashaal; Asmaa A. Abo Elqasem; Lina A. Abou El-Khashab; Hend M. El-Menyawy; Basma M. Abou El-Nour; Eman M. Abdullah; Asmaa M. Abdalkareem; Rawda A. Al-gebaly; Asmaa M. El-sayed; Ghada R. Mabrok; Rawda R. Mahmoud; Dina A. Ali; et al. (Biologia, 2024)
In recent years, there has been a growing interest in exploring novel natural sources for antioxidant and anti-inflammatory agents, driven by the need for alternative therapeutic strategies with fewer side effects. This study investigates the potential of the Biomphalaria alexandrina snail as a valuable model organism to evaluate the antioxidant and anti-inflammatory properties of Sarcophaga argyrostoma larval hemolymph. The choice of B. alexandrina snails as a model is based on its ecological relevance and physiological similarities to other organisms, supporting well-established use in ecological and physiological research, as well as it provides a valuable platform for such investigations. Ultimately, this study may open avenues for the development of innovative and sustainable therapeutic interventions rooted in the rich biodiversity of the natural world. The experimental design involves the extraction of hemolymph from S. argyrostoma larvae, followed by a comprehensive analysis of its antioxidant capacity and anti-inflammatory effects using adult snails. Various biochemical assays, including total antioxidant capacity, immunomodulatory markers and histological investigation, will be employed to assess the bioactive potential of the hemolymph. The outcomes of this research can be attributed to the identification of the anti-oxidant and anti-inflammatory effects of hemolymph. This effect was observed through the reduction of oxidative stress and proinflammatory mediators, impacting the biological activities of the snails. The study is the first to shed light on the potential benefits of S. argyrostoma larval hemolymph using an animal model, showcasing its ability to mitigate oxidative and inflammatory responses within the biological context of the snails.

Synthesis and molecular docking study of α-aminophosphonates as potential multi-targeting antibacterial agents - Rana R. Neiber; Nadia A. Samak; Jianmin Xing; Elshaymaa I. Elmongy; Ahmed A. Galhoum; Ibrahim El-Tantawy El Sayed; Eric Guibal; Jiayu Xin; Xingmei Lu (Journal of Hazardous Materials, 2024)

Dietary flaxseed cake influences on performance, quality, and sensory attributes of eggs, serum, and egg trace minerals of laying hens - Youssef A. Attia; Ahmed A. Al-Sagan; El-Sayed O. S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Al-Abdullatif; Rashed A. Alhotan; Salem R. Alyileili; Heba A. Shehata; Vincenzo Tufarelli (Tropical Animal Health and Production, 2024)

Mesenchymal stem cell transplantation in burn wound healing: uncovering the mechanisms of local regeneration and tissue repair - Mohamed E. El-Sayed; Ahmed Atwa; Ahmed R. Sofy; Yasser A. Helmy; Khaled Amer; Mohamed G. Seadawy; Sayed Bakry (Histochemistry and Cell Biology, 2024)
Burn injuries pose a significant healthcare burden worldwide, often leading to long-term disabilities and reduced quality of life. To explore the impacts of the transplantation of mesenchymal stem cells (MSCs) on the healing of burns and the levels of serum cytokines, 60 fully grown Sprague–Dawley rats were randomly divided into three groups ( n = 20 each): group I (control), group II (burn induction), and group III (burn induction + bone marrow (BM)-MSC transplantation). Groups II and III were further divided into four subgroups ( n = 5 each) based on euthanasia duration (7, 14, 21, and 28 days post transplant). The experiment concluded with an anesthesia overdose for rat death. After 7, 14, 21, and 28 days, the rats were assessed by clinical, laboratory, and histopathology investigations. The results revealed significant improvements in burn healing potentiality in the group treated with MSC. Furthermore, cytokine levels were measured, with significant increases in interleukin (IL)-6 and interferon alpha (IFN) observed, while IL-10 and transforming growth factor beta (TGF-β) decreased at 7 days and increased until 28 days post burn. Also, the group that underwent the experiment exhibited increased levels of pro-inflammatory cytokines and the anti-inflammatory cytokine IL-10 when compared to the control group. Histological assessments showed better re-epithelialization, neovascularization, and collagen deposition in the experimental group, suggesting that MSC transplantation in burn wounds may promote burn healing by modulating the immune response and promoting tissue regeneration.

Cryopreservation of Anopheles stephensi (MOSQUITO) EGGS: EFFECTS ON GENOTYPIC AND PHENOTYPIC CHARACTERISTICS - Morgan Douglas; Ehud Inbar; Igor Sharakov; Najib M. El-Sayed; Ashton T. Belew; James Overby; Steve Matheny; Fantahun Addisu; Yonas Abebe; Dimitri Koutzoumis; Kerri Springer; Abraham Eappen; et al. (Cryobiology, 2023)

Automated diagnosis of EEG abnormalities with different classification techniques - Essam Abdellatef; Heba M. Emara; Mohamed R. Shoaib; Fatma E. Ibrahim; Mohamed Elwekeil; Walid El-Shafai; Taha E. Taha; Adel S. El-Fishawy; El-Sayed M. El-Rabaie; Ibrahim M. Eldokany; Fathi E. Abd El-Samie (Medical & Biological Engineering & Computing, 2023)

Physiological and Agronomic Responses and Nutrient Uptake of Soybean Genotypes Cultivated Under Various Sowing Dates - Mostafa G. Shahin; Hani S. Saudy; Mohamed E. El-Bially; Wasfi R. Abd El-Momen; Yasser A. El-Gabry; Gomaa A. Abd El-Samad; Amany N. Sayed (Journal of Soil Science and Plant Nutrition, 2023)
Late or early sowing subjecting crop plants to stress conditions, this is simulating the climatic change effects. The global warming and climate change are critical issues in agriculture since progressive rise in temperature leads to exposure the crops to heat stress, hence low productivity. Since weather conditions are uncontrollable, it is impossible to modulate their negative impacts against crop growth and development. However, scientists should not be handcuffed about this serious problem. So, in open field conditions, the performance of some soybean genotypes was evaluated under different sowing dates. Along the two seasons of 2019 and 2020, field experiments were designed in a split-plot design using three replicates to evaluate the performance of four soybean genotypes (Giza-21, Giza-35, Giza-111, and Crawford) under four sowing dates (15th April, 30th April, 15th May, and 30th May). Various physiological and growth traits, yield attributes, seed nutrient contents, and oil and protein contents were estimated. Sowing Crawford (in both seasons) and Giza-35 (in the first season) on 15th April as well as Giza-111 either on 30th April or 15th May produced the highest catalase activity. In plots sown on 30th April, Crawford and Giza-21 (in the first season) and Giza-111 (in both seasons) exhibited the highest leaves area plant −1 . Plots sown by Giza-111 on 30th April was the potent interaction for enhancing seed yield in both seasons. Under any sowing date in the second season and the sowing date of 30th April in the first season, Giza-111 was the effective genotype for recording the maximum seed oil content. For adopting a specific stress condition scenario, it is advisable to insert Giza-111 as an effective gene pool to improve soybean genotypes under unfavorable conditions, expressed in sowing dates.

Myco-fabricated ZnO nanoparticles ameliorate neurotoxicity in mice model of Alzheimer’s disease via acetylcholinesterase inhibition and oxidative stress reduction - Hanan A. Abd Elmonem; Reham M. Morsi; Doaa S. Mansour; El-Sayed R. El-Sayed (BioMetals, 2023)
Alzheimer’s disease (AD) is one of the primary health problems linked to the decrease of acetylcholine in cholinergic neurons and elevation in oxidative stress. Myco-fabrication of ZnO-NPs revealed excellent biological activities, including anti-inflammatory and acetylcholinesterase inhibitory potentials. This study aims to determine if two distinct doses of myco-fabricated ZnO-NPs have a positive impact on behavioral impairment and several biochemical markers associated with inflammation and oxidative stress in mice that have been treated by aluminum chloride (AlCl 3 ) to induce AD. Sixty male mice were haphazardly separated into equally six groups. Group 1 was injected i.p. with 0.5 ml of deionized water daily during the experiment. Mice in group 2 received AlCl 3 (50 mg/kg/day i.p.). Groups 3 and 4 were treated i.p. with 5 and 10 mg/kg/day of ZnO-NPs only, respectively. Groups 5 and 6 were given i.p. 5 and 10 mg/kg/day ZnO-NPs, respectively, add to 50 mg/kg/day AlCl 3 . Results showed that the AlCl 3 caused an increase in the escape latency time and a reduction in the time spent in the target quadrant, indicating a decreased improvement in learning and memory. Moreover, acetylcholinesterase enzyme (AChE) activity and malondialdehyde (MDA), tumor necrosis factor-alpha (TNF-α), and interleukin 1β (IL-1β) levels were significantly increased, and the content of glutathione (GSH), activities of superoxide dismutase (SOD), catalase (CAT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), as well as levels of serotonin and dopamine, were decreased in brain tissues only in AlCl 3 treated mice. However, treatment of mice with myco-fabrication of ZnO-NPs at doses of 5 or 10 mg/kg improves learning and memory function through ameliorate all the previous parameters in the AD mice group. The low dose of 5 mg/kg is more effective than a high dose of 10 mg/kg. In accordance with these findings, myco-fabricated ZnO-NPs could enhance memory and exhibit a protective influence against memory loss caused by AlCl 3 .

Withdrawal notice to “Seasonal monitoring of the River Nile in the area of Greater Cairo using a combined approach of certain chemical criteria and macroinvertebrates matrices” [Limnologica 103 (2023) 126119] - Hanaa M.M. El-Khayat; Mohamed R. Habib; Wafaa A. Mohammed; Khaled M. Zayed; Sara S.M. Sayed (Limnologica, 2023)

WITHDRAWN: Seasonal monitoring of the River Nile in the area of Greater Cairo using a combined approach of certain chemical criteria and macroinvertebrates matrices - Hanaa M.M. El-Khayat; Mohamed R. Habib; Wafaa A. Mohammed; Khaled M. Zayed; Sara S.M. Sayed (Limnologica, 2023)

Cellophane packaging treated with nano silica is superior to polyethylene in reducing stored irradiated flour from Tribolium confusum infestation - T. S. El sayed; S. A. Rizk; R. M. Sayed (International Journal of Tropical Insect Science, 2023)
Most packaged food products are attacked and penetrated by insects. Causing reducing food quality. Since, different ways are investigated for controlling stored-product pests without application of chemical methods. So, the present study included laboratory methods to evaluate the effectiveness of two packaging materials, polyethylene and cellophane with silica nano particles to prevent or minimize the insect infestation and grain wastage resulting by the attack of wheat grain by confused flour beetle, Tribolium confusum . Studies made to determine the protecting capacity of the two packaging materials through assessing some parameters, number of adults infested poly ethelene and cellophane bags, percentage weight loss of grains, the results revealed that cellophane was the better packaging material than polyethelene, so polyethylene was the susceptible packaging material because it had maximum number of holes as a result penetrations by insects into them. Also, treatment the two types with packaging materials with different concentrations of nano silica protect the treated packaging materials from insect infestation and the protection increase with the increase of the concentration of silica nano particles

Implications of BCRP modulation on PTZ-induced seizures in mice: Role of ko143 and metformin as adjuvants to lamotrigine - Sahar A. Harby; Nehal A. Khalil; Norhan S. El-Sayed; Eman H. Thabet; Samar R. Saleh; Mona Hassan Fathelbab (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Blood–brain barrier (BBB) efflux transporters' overexpression hinders antiepileptic drug brain entry. Breast cancer resistance protein (BCRP) is a major BBB efflux transporter. In the present work, BCRP's role as a mechanism that might contribute to drug-resistant epilepsy (DRE) in a mouse model of acute seizures was studied with further assessment of the effect of its inhibition by ko143 and metformin (MET) on lamotrigine (LTG) bioavailability and efficacy. 42 male mice divided into 6 groups: G1: Normal control, G2: LTG-injected healthy mice: LTG 20 mg/kg i.p., G3: Acute seizures (A.S) mice: Pentylenetetrazole (PTZ) 50 mg/kg i.p., G4: LTG-treated A.S mice: LTG 20 mg/kg + PTZ 50 mg/kg i.p., G5: Ko143 + LTG treated A.S mice: Ko143 15 mg/kg i.p. before LTG + PTZ, G6: MET + LTG treated A.S mice: MET 200 mg/kg i.p. before LTG + PTZ. Seizures severity, serum, brain LTG, and brain BCRP were assessed. PTZ group experienced the highest seizure frequency and brain BCRP expression. Ko143 and MET groups showed a significant decrease in brain BCRP with subsequent improvement in brain LTG level and better seizure control. BCRP has a significant role in epilepsy resistance and its inhibition with ko143 or MET adds value to DRE management.

Metabolic Analysis of Methylenetetrahydrofolate Reductase Single Nucleotide Polymorphisms (MTHFR 677C<T and MTHFR 1298A<C), Serum Folate and Vitamin B12 in Neural Tube Defects - Mohammed H. Hassan; Mohamed A. Raslan; Mena Tharwat; Hala M. Sakhr; Eslam El-Sayed El-Khateeb; Shimaa Fathy Sakr; Hesham H. Ameen; Ali R. Hamdan (Indian Journal of Clinical Biochemistry, 2023)

Ultrasonography and computer-assisted assessment of postpartum uterine echotexture and its relationship with peripheral oxidative stress biomarkers in goats - Haney Samir; Faten Radwan; Ahmed R.M. El-Khawagah; Mohamed Kandiel; Mohamed A.I. El Sayed; Ahmed Elfadadny; Aly Karen; Hossam R. El-Sherbiny (Small Ruminant Research, 2023)

Interactive adverse effects of low-density polyethylene microplastics on marine microalga Chaetoceros calcitrans - Hoda H. Senousy; Hanan M. Khairy; Heba S. El-Sayed; Eman R. Sallam; Mohamed A. El-Sheikh; Mostafa E. Elshobary (Chemosphere, 2023)

Protective efficacy of dietary natural antioxidants on microplastic particles-induced histopathological lesions in African catfish (Clarias gariepinus) - Alaa El-Din H. Sayed; Mervat N. Hana; Mohamed Hamed; Hany M. R. Abdel-Latif; Jae-Seong Lee; Hamdy A. M. Soliman (Environmental Science and Pollution Research, 2022)
Microplastic particles (MPs) are a common environmental pollutant easily ingested by fish in aquaculture. The current study evaluated the protective efficacies of some antioxidant, e.g., lycopene, citric acid, and chlorella, against the toxic effects of MP ingestion by Clarias gariepinus using histopathological biomarkers. Five experimental groups were established, a control group receiving only a standard diet, a group exposed to 500 mg/kg MP concomitant with the standard diet, and three antioxidant groups exposed to MPs plus either lycopene (500 mg/kg), citric acid (30 g/kg), or chlorella (50 g/kg) in the standard diet. After 15 days, fish were sacrificed for histological and histochemical examinations. Histological analysis of the kidney for group 2 (fed 500 mg/kg MPs alone) revealed distributed tissue dissociation, regional glomerular hypertrophy or shrinkage, melanomacrophage accumulation, and expansion of Bowman’s space, while liver tissue exhibited dilation and rupture of the central vein wall, hemorrhage, cytoplasmic vacuolation, and cellular necrosis or apoptosis. Fish exposed to MPs also exhibited connective tissue fiber accumulation around renal blood vessels, renal tubules, the central hepatic vein, hepatic blood sinusoids, and serosal, muscle, and submucosal layers of the intestine. In addition, MP exposure reduced carbohydrate (mainly glycogen) contents in the brush borders and basement membranes of renal tubules, glomeruli, and intestinal tissues as well as in the cytoplasm of hepatocytes. These signs of renal, hepatic, and intestinal histopathology were fully or partially reversed by dietary lycopene, chlorella, or citric acid. Enhancing dietary antioxidants is an effective strategy for preventing MP toxicity in Clarias gariepinus in aquaculture.

Cytotoxic potential of three Sabal species grown in Egypt: a metabolomic and docking-based study - Seham S. El-Hawwary; Fatema R. Saber; Hanan M. Abd Almaksoud; Hanan Elimam; Ahmed M. Sayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

A new cycloartane triterpene and other phytoconstituents from the aerial parts of Euphorbia dendroides - Ahmed R. Hassan; Ahmed Ashour; Yhiya Amen; Maki Nagata; Sayed A. El-Toumy; Kuniyoshi Shimizu (Natural Product Research, 2022)

Silver nanoparticles as a viricidal agent to inhibit plant-infecting viruses and disrupt their acquisition and transmission by their aphid vector - Ahmed Y. El Gamal; Mohamed R. Tohamy; Mohamed I. Abou-Zaid; Mahmoud M. Atia; Tarek El Sayed; Khaled Y. Farroh (Archives of Virology, 2022)

Metabolic resistance to organophosphate insecticides in natural populations of the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) in Egypt and molecular identification of mitotypes - El-Sayed H. Shaurub; Jorge R. Paredes-Montero; Judith K. Brown; Haggag S. Zein; Amr A. Mohamed (Phytoparasitica, 2021)

Genetic polymorphism of lysyl oxidase, glutathione S-transferase M1, glutathione-S-transferase T1, and glutathione S-transferase P1 genes as risk factors for lung cancer in Egyptian patients - Sahar E. M. El-Deek; Soad M. Abdel-Ghany; Randa S. Hana; Aliaa A. R. Mohamed; Naglaa T. El-Melegy; Ayat A. Sayed (Molecular Biology Reports, 2021)

Temporal and spatial variations of surface water quality in the Nile River of Damietta Region, Egypt - Mohamed El Sayed Taher; Ahmed M. Ghoneium; Russell R. Hopcroft; Wael S. ElTohamy (Environmental Monitoring and Assessment, 2021)

Mapping and assessing limestone as a raw material for the cement industry using satellite data: a case study of areas between Riyadh and Al Kharj, Saudi Arabia - El Sayed Selim; Hatem Aboelkhair; Eid R. Aboezz (Arabian Journal of Geosciences, 2020)

Developmental toxicity of carbon nanoparticles during embryogenesis in chicken - Dalia H. Samak; Yasser S. El-Sayed; Hazem M. Shaheen; Ali H. El-Far; Mohamed E. Abd El-Hack; Ahmed E. Noreldin; Karima El-Naggar; Sameh A. Abdelnour; Essa M. Saied; Hesham R. El-Seedi; Lotfi Aleya; Mohamed M. Abdel-Daim (Environmental Science and Pollution Research, 2020)

Phenolic profiling and anti-Alzheimer’s evaluation of Eremobium aegyptiacum - Mona M. Marzouk; Lamyaa F. Ibrahim; Ali M. El-Hagrassi; Dalia B. Fayed; Ahmed Elkhateeb; El-Sayed S. Abdel-Hameed; Sameh R. Hussein (Advances in Traditional Medicine, 2020)

Cyclosporin A activates human hepatocellular carcinoma (HepG2 cells) proliferation: implication of EGFR-mediated ERK1/2 signaling pathway - Mohammed E. Abo-El Fetoh; Gouda K. Helal; I. G. Saleh; M. Ewees; Mohamed ElShafey; Mohamed R. Elnagar; El-Sayed Akool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

An integrated water quality assessment of Damietta and Rosetta branches (Nile River, Egypt) using chemical and biological indices - Seleim M. El Sayed; Mahmoud H. Hegab; Hesham R. A. Mola; Nasr M. Ahmed; Mohame E. Goher (Environmental Monitoring and Assessment, 2020)

Newly isolated marine bacterial exopolysaccharides enhance antitumor activity in HepG2 cells via affecting key apoptotic factors and activating toll like receptors - Shaymaa M.M. Yahya; Salma M. Abdelnasser; Ahmad R. Hamed; Osama H. El Sayed; Mohsen S. Asker (Molecular Biology Reports, 2019)

RETRACTED ARTICLE: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2019)

Isotherm and kinetic studies on the adsorption of humic acid molecular size fractions onto clay minerals - Mohamed E. A. El-Sayed; Moustafa M. R. Khalaf; James A. Rice (Acta Geochimica, 2019)

Attenuation potentials of royal jelly against hydroxyurea-induced infertility through inhibiting oxidation and release of pro-inflammatory cytokines in male rats - Hossam G. Tohamy; Dina R. Gad El-Karim; Yasser S. El-Sayed (Environmental Science and Pollution Research, 2019)

A new flavonol glycoside and other flavonoids from the aerial parts of Taverniera aegyptiaca - Ahmed R. Hassan; Khadiga F. Amer; Sayed A. El-Toumy; John Nielsen; Søren Brøgger Christensen (Natural Product Research, 2019)

LC-MS-based metabolomic profiling of Lepidium coronopus water extract, anti-inflammatory and analgesic activities, and chemosystematic significance - Ahmed Elkhateeb; Mona El-Shabrawy; Rehab F. Abdel-Rahman; Mona M. Marzouk; Ahmed H. El-Desoky; El-Sayed S. Abdel-Hameed; Sameh R. Hussein (Medicinal Chemistry Research, 2019)

Nutritive utilization of Moringa oleifera tree stalks treated with fungi and yeast to replace clover hay in growing lambs - K. Z. Kewan; F. A. Salem; A. Z. M. Salem; A. R. Abdou; H. M. El-Sayed; S. S. Eisa; E. A. Zaki; N. E. Odongo (Agroforestry Systems, 2019)

Influence of different microalgal diets on gonadal development of the carpet shell clam Ruditapes decussatus broodstock - Ahmed S. A. Abbas; Eman El-Wazzan; Amal R. Khafage; Abdel-Fattah M. El-Sayed; Fatma A. Abdel Razek (Aquaculture International, 2018)

Modelling of land-use changes and their effects by climate change at the southern region of Port Said governorate, Egypt - Mohamed A. E. R. Hassan; El-Sayed E. Omran (Modeling Earth Systems and Environment, 2017)

Experimental study on the utilization of dune sands as a construction material in the area between Jeddah and Mecca, Western Saudi Arabia - El-Sayed Sedek Abu Seif; Abdullah R. Sonbul; Bader Abdo Hasan Hakami; E. K. El-Sawy (Bulletin of Engineering Geology and the Environment, 2016)

Occurrence of copper-complexing ligands in the coastal sediments of eastern Red Sea - R. Al-Farawati; M. A. El Sayed; Y. A. Shaban; A. J. Turki (Arabian Journal of Geosciences, 2016)

Antioxidant and anti-inflammatory effects of flavocoxid in high-cholesterol-fed rabbits - Ahmed R. El-Sheakh; Hamdy A. Ghoneim; Ghada M. Suddek; El-Sayed M. Ammar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Giant reed for selenium phytoremediation under changing climate - Hassan R. El-Ramady; Neama Abdalla; Tarek Alshaal; Ahmed S. Elhenawy; Mohamed S. Shams; Salah E.-D. A. Faizy; El-Sayed B. Belal; Said A. Shehata; Mohamed I. Ragab; Megahed M. Amer; Miklós Fári; Attila Sztrik; et al. (Environmental Chemistry Letters, 2015)

Invasive Vespula Wasps Utilize Kairomones to Exploit Honeydew Produced by Sooty Scale Insects, Ultracoelostoma - Robert L. Brown; Ashraf M. El-Sayed; C. Rikard Unelius; Jacqueline R. Beggs; David M. Suckling (Journal of Chemical Ecology, 2015)

Optimization of submerged fermentation conditions for immunosuppressant mycophenolic acid production by Penicillium roqueforti isolated from blue-molded cheeses: enhanced production by ultraviolet and gamma irradiation - Ahmed A. Ismaiel; Ashraf S. Ahmed; El-Sayed R. El-Sayed (World Journal of Microbiology and Biotechnology, 2014)

Evening primrose oil and celecoxib inhibited pathological angiogenesis, inflammation, and oxidative stress in adjuvant-induced arthritis: novel role of angiopoietin-1 - R. M. El-Sayed; Y. M. Moustafa; M. F. El-Azab (Inflammopharmacology, 2014)

Alleviation of Dimethylnitrosamine-Induced Liver Injury and Fibrosis by Supplementation of Anabasis articulata Extract in Rats - Azza M. Mohamed; Mohga S. Abdalla; Maha Z. Rizk; El-Sayed M. E. Mahdy; Abdel-Razik H. Farrag; Fatma S. El-Sharabasy; Hanan F. Aly; Mohamed R. Mohamed (Indian Journal of Clinical Biochemistry, 2014)

Efficient pan-sharpening of satellite images with the contourlet transform - Mohamed R. Metwalli; Ayman H. Nasr; Osama S. Faragallah; El-Sayed M. El-Rabaie; Alaa M. Abbas; Saleh A. Alshebeili; Fathi E. Abd El-Samie (International Journal of Remote Sensing, 2014)

A new isoflavone from Blepharis ciliaris of an Egyptian origin - Mohamed A. El-Shanawany; Hanaa M. Sayed; Sabrin R. M. Ibrahim; Marwa A. A. Fayed; Mohamed M. Radwan; Samir A. Ross (Medicinal Chemistry Research, 2013)

Hall and Porous Boundaries Effects on Peristaltic Transport Through Porous Medium of a Maxwell Model - Soliman R. El Koumy; El Sayed I. Barakat; Sara I. Abdelsalam (Transport in Porous Media, 2012)

In vitro and in vivo neo-cartilage formation by heterotopic chondrocytes seeded on PGA scaffolds - A. Lohan; U. Marzahn; K. El Sayed; A. Haisch; B. Kohl; R. D. Müller; W. Ertel; G. Schulze-Tanzil; T. John (Histochemistry and Cell Biology, 2011)

Bioactive lipids and antioxidant properties of wild Egyptian Pulicaria incise, Diplotaxis harra, and Avicennia marina - M. F. Ramadan; M. M. A. Amer; H. T. Mansour; K. M. Wahdan; R. M. El-Sayed; S. El-Sanhoty; W. A. El-Gleel (Journal of Consumer Protection and Food Safety, 2009)

Pheromone Disruption of Argentine Ant Trail Integrity - D. M. Suckling; R. W. Peck; L. M. Manning; L. D. Stringer; J. Cappadonna; A. M. El-Sayed (Journal of Chemical Ecology, 2008)

Follicular dendritic cells stimulated by collagen type I develop dendrites and networks in vitro - M. E. El Shikh; R. M. El Sayed; J. G. Tew; A. K. Szakal (Cell and Tissue Research, 2007)

(11Z,13E)-Hexadecadien-1-yl Acetate: Sex Pheromone of the Grass Webworm Herpetogramma licarsisalis—Identification, Synthesis, and Field Bioassays - Andrew R. Gibb; D. Max Suckling; Ashraf M. El-Sayed; Björn Bohman; C. Rikard Unelius; Jennifer J. Dymock; Michelle L. Larsen; Bruce E. Willoughby (Journal of Chemical Ecology, 2007)

Estimation of frequency dependent coda wave attenuation structure at the vicinity of Cairo Metropolitan Area - Salah El-Hadidy; M. E. Mohamed Adel; Ahmed Deif; Ahmed Sayed Abu El-Ata; S. R. Moustafa Sayed (Acta Geophysica, 2006)

Identification of Sex Pheromone Components of a New Zealand Geometrid Moth, the Common Forest Looper Pseudocoremia suavis, Reveals a Possible Species Complex - A. R. Gibb; D. Comeskey; L. Berndt; E. G. Brockerhoff; A. M. El-Sayed; H. Jactel; D. M. Suckling (Journal of Chemical Ecology, 2006)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Optimization of Pheromone Lure and Trap Characteristics for Currant Clearwing, Synanthedon tipuliformis - D. M. Suckling; A. R. Gibb; G. M. Burnip; C. Snelling; J. De Ruiter; G. Langford; A. M. El-Sayed (Journal of Chemical Ecology, 2005)

Relative Attractiveness of (10E)-Dodecen-1-yl Acetate and (4E,10E)-Dodecadien-1-yl Acetate to Male Spotted Tentiform Leafminers Phyllonorycter blancardella (F.) - A. M. El-Sayed; L. I. Wainman; E. M. Santangelo; C. R. Unelius; R. M. Trimble (Journal of Chemical Ecology, 2004)